Market and other factors affecting farm-specific production efficiency in poultry production in Vietnam - Jabbar, M.A.; Akter, S. (Informa UK Limited, 2006)
Stochastic frontier production function was used to assess technical efficiency and its determinants for a stratified sample of 1118 poultry farms in Vietnam for which data were collected in 1999. In general there are significant differences in the production behaviour and efficiency level between the North and the South, among farms producing different breeds of poultry, between mixed and specialized poultry farms, between household and commercial farms, and among producers located in different agro-ecological regions. Sale at market place rather than at farm gate, market distance and flock size significantly reduced inefficiency in both the regions. Contract farming or sale, number of visits by extension staff, family labor supply, land size and education of household had significantly reduced inefficiency in the North but had no significant effect in the South. The direction and significance of influence on efficiency differ between the two regions for credit use, inputs from government, ratio of home produced of crude feed, producer age and gender of household head. Therefore, opportunities exist for improving average efficiency through interventions in a number of product and input market domains and household characteristics that may improve access to information, technology and management decisions.